The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.55870/tgv.v40i2.2683
|View full text |Cite
|
Sign up to set email alerts
|

Neutralitet och muslimska kvinnors slöja

Abstract: This article takes the ruling of the European Court of Justice concerning the so-called neutral clothing policy, within private companies, as a starting point. The ruling facilitates prohibition of visible religious, philosophical and political signs. The resulting neutrality policies are studied from the point of view of their consequences, both concrete and emotional ones, as well as how they are perceived and experienced among Muslim women in Sweden. One of the concrete consequences appeared in an employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…For example, Karlsson Minganti (2014) sheds light on a younger generation of men and women using comedy as a tool to play with negative stereotypes of Muslims as well as young Muslim fashion entrepreneurs creatively countering stereotypes about the hijab (Karlsson Minganti and Österlind, 2016). Muslim women who, through activism, engage in antiracist struggle, taking on public debates and policies regarding Muslims and Islam in Sweden, have also highlighted the backlash they receive (Jakku, 2019). Reports and studies have also indicated how people who have experienced antimuslim racism use certain coping strategies including hiding ones religious identity and being overly conscious of one's behavior (Abdullahi, 2016;Olseryd et al, 2021).…”
Section: From the Discourses Of The Submissive Muslim Woman To The Da...mentioning
confidence: 99%
“…For example, Karlsson Minganti (2014) sheds light on a younger generation of men and women using comedy as a tool to play with negative stereotypes of Muslims as well as young Muslim fashion entrepreneurs creatively countering stereotypes about the hijab (Karlsson Minganti and Österlind, 2016). Muslim women who, through activism, engage in antiracist struggle, taking on public debates and policies regarding Muslims and Islam in Sweden, have also highlighted the backlash they receive (Jakku, 2019). Reports and studies have also indicated how people who have experienced antimuslim racism use certain coping strategies including hiding ones religious identity and being overly conscious of one's behavior (Abdullahi, 2016;Olseryd et al, 2021).…”
Section: From the Discourses Of The Submissive Muslim Woman To The Da...mentioning
confidence: 99%